Evaluation of some physical, chemical and bacteriological characteristics in Kirkuk city - Aseel H. Mahdi; Yassien H. Owaied AL-Juboory (Tikrit Journal of Pure Science, 2022)
The present study aimed to conduct a field study on the water of eight wells in different areas of Kirkuk city. The modeling was done on a monthly basis, starting from November 2019 until April 2020. The study included measuring some physical factors (water temperature, electrical conductivity, total dissolved solids) and some chemical factors (pH, dissolved oxygen, biological oxygen demand, total alkalinity, total hardness, calcium hardness, magnesium hardness, sodium ion, sulfate, Chlorides, nitrates, phosphates. Also, a study was conducted on the bacterial contamination of groundwater wells, which included the total number of colonies of the total plate count, the total number of coliforms, and the total numbers of Faecal coliform Bacteria. The results showed that the air temperatures ranged between (16-18.6)Co, while the wells' water temperatures were within the warm water and their rates ranged between (22.5-24.8) Co. An increase in the sulfate values ​​was observed in most of the study wells, while nitrates recorded low values. On the bacteriological side, it was found that most of the wells were not contaminated. The reason is due.to the depth of the wells and their distance from the sources of pollution.